Fintech Adoption and Customer Loyalty in Indonesian Banking: The Mediating Role of Trust in the Perceived Benefit–Risk Trade-Off - Erika, Ria; Prastowo, Sugeng Lubar; Sutarjo, Sutarjo (PT. Batari Edu Calya, 2025)
Financial technology (fintech) is reshaping banking by offering efficiency and accessibility, yet customer loyalty depends on balancing perceived benefits and risks. This study examines how fintech adoption influences loyalty through the mediating role of trust, with perceived benefit and perceived risk as antecedents. A quantitative survey of 150 Bank Rakyat Indonesia (BRI) customers in Tangerang was analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results show that fintech adoption significantly increases perceived benefits, which positively affect trust, while perceived risk exerts a negative but insignificant influence. Trust does not directly predict loyalty but partially mediates the benefit–loyalty relationship. These findings highlight the benefit–risk trade-off in fintech adoption and underscore the importance of enhancing trust to sustain customer loyalty. The study contributes to fintech adoption theory and provides practical guidance for banks to improve customer experience while mitigating risks.